Development of an Innovative History Learning Model Based on Gusjigang Values at MAN 1 Kudus - Nadia Kusuma Dewi; R. Soeharso (Historia, 2026)
History learning still faces challenges such as low reading interest, varied student engagement, and the lack of systematic integration of local wisdom values. This study aims to develop an innovative history learning model based on Gusjigang values at MAN 1 Kudus. The method used is Research and Development (R&D), limited to the needs analysis and model design stages. Data were collected through semi-structured interviews with a history teacher and analyzed using descriptive qualitative analysis. The results show that history learning requires a flexible and varied model that integrates character education and local wisdom values. Gusjigang values are considered relevant to be integrated into contextual history learning. This study produces a conceptual learning model design to support meaningful and contextual history learning.